Efektifitas Metode Membuat Kalimat Dalam Pembelajaran Bahasa di Pondok Pesantren Muhammadiyah At-Tajdid Cepu - Fahimatus Sazkiah, Fahimatus Sazkiah; Helmi Gunawan, Helmi Gunawan (Al Fattah Ejournal Sma Al Muhammad Cepu, 2023)
The purpose of this study was to determine the effectiveness of using the sentence-making method in language learning and to find out what are the impacts of using the sentence-making method in language learning at the At-Tajdid Cepu Islamic Boarding School. Is a type of research using descriptive qualitative research. The collection of data related to this study was carried out using questionnaires and observation methods. The data analysis techniques used include 1) data collection, 2) data reduction, 3) data display, and 4) conclusion drawing. The results of the study show that the method of making sentences in language learning at the At-Tajdid Cepu Islamic Boarding School has pretty good results. Which indicates that the method is quite effective. The advantages of this method were also found, namely, students were more accustomed to composing a sentence so that they were able to apply it theoretically and practically. The drawback found in this method is that this method tends to focus on placing vocabulary in a sentence without paying more attention to whether the arrangement of the sentence is correct or not.